Pengaruh Lama Pemanasan pada Penurunan Kualitas Mutu Minyak Goreng Sawit Komersial: Effect of Heating Duration on The Deterioration of Commercial Palm Cooking Oil Quality - Telaumbanua, Melati Claudia; Utama, Qabul Dinanta (Jurnal Teknologi dan Mutu Pangan, 2024)
The quality of palm cooking oil is an important parameter that must be considered. Repeated use of cooking oil at high temperatures and prolonged exposure can change the physical characteristics of the oil and result in oil degradation and increase polar components such as triacylglycerol dimers and oligomers that can increase the risk of heart and gastrointestinal diseases. This study aims to analyze the deterioration of palm cooking oil during the frying process. Cooking oil samples were heated at 150-160 â„ƒ for 45, 60 and 90 minutes. This study used the observation method of free fatty acid content, peroxide number and total oxidative value (TOTOX value). The results showed that heating at a temperature of 150-160 â„ƒ caused a decrease in quality characterized by an increase in free fatty acid content, peroxide number and TOTOX value. Based on the results of the research conducted, it shows that of the three samples of packaged palm cooking oil tested, packaged palm cooking oil Y is the best quality oil by having the lowest fatty acid content, peroxide number and TOTOX value among packaged palm cooking oils X and Z. This study makes an important contribution in recognizing the negative impact of repeated use of palm cooking oil at high temperatures, by identifying deterioration through observations of free fatty acid content, peroxide number, and TOTOX value, which have significant implications for cardiovascular and gastrointestinal health.